Endohelminth fauna of teleost fishes from coasts of Şile region of the Black sea - Aslan Çelık B. (Sciendo, 2021)
A total of 508 fish specimens belonging to 19 species collected in the coast of Şile region of the Black sea were examined to detect the presence of endohelminths. Of this, 357 (70.27%) were found to be infected with parasites. 15 distinct helminths species were recovered including four species of nematodes, seven digenean species, one species of cestodes and three species of acanthocephalans. It was also determined that the species of nematode Hysterothylacium aduncum was the most common parasite and the most diverse endohelminth fauna was found in Gobius niger and Solea vulgaris, with five species. Furthermore, it should be noted that Capillaria gracilis is reported for the first time from the Turkish coasts. The infection rates, hosts, and parasites are listed in this paper.